2006
DOI: 10.1177/1054773806287051
|View full text |Cite
|
Sign up to set email alerts
|

Hand Dermatitis Risk Factors Among Clinical Nurses in Japan

Abstract: The purpose of this study was to establish hand dermatitis (HD) risk factors among Japanese nurses. A questionnaire was administered to 1,162 clinical nurses, from whom 860 replies were received (response rate of 74.0%). Their overall HD prevalence was 53.3%. Several risk factors were identified: using latex gloves (odds ratio [OR] 1.9), allergies in adulthood (OR 2.7), urticaria as an adult (OR 1.5), atopic dermatitis as an adult (OR 2.7), any allergies to latex products (OR 5.2), skin irritation following co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 16 publications
2
36
0
2
Order By: Relevance
“…The 1‐year prevalence of HE in those Japanese studies, which were performed in an occupational setting, was reported to be much higher than the estimated prevalence of 10% found in the general population . The rates in the Japanese occupational setting were 35% in 305 nurses at a teaching hospital, 53.3% in 860 clinical nurses and 36.2% in 528 dental workers . Arase et al .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The 1‐year prevalence of HE in those Japanese studies, which were performed in an occupational setting, was reported to be much higher than the estimated prevalence of 10% found in the general population . The rates in the Japanese occupational setting were 35% in 305 nurses at a teaching hospital, 53.3% in 860 clinical nurses and 36.2% in 528 dental workers . Arase et al .…”
Section: Introductionmentioning
confidence: 90%
“…HE is often work‐related, with a high prevalence especially in occupations involving wet work, such as nursing, medical and service work . In Japan, three population‐based studies have been performed . The 1‐year prevalence of HE in those Japanese studies, which were performed in an occupational setting, was reported to be much higher than the estimated prevalence of 10% found in the general population .…”
Section: Introductionmentioning
confidence: 99%
“…1997, Forrester & Roth 1998, Jungbauer et al. 2005), the type of agents used for hand washing and the unit of employment (Smith et al. 2006, Flyvholm et al.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, the prevalence of HD in nurses varies considerably around the world, with reports of 17.7% in mainland China [6], 20% in the United Kingdom [1], 22.1% in Hong Kong [7], 30% in Denmark [8], 31% in the Netherlands [9], 31% in South Korea [10], 40% in Germany [3], 46% in Poland [11], 50% in Australia [12], 53.3% in Japan [13] and 55% in the United States [14]. It also varies according to the way HD is detected (self-reported, appearance of symptoms or clinical observation, or formal diagnosis by a clinician).…”
Section: Discussionmentioning
confidence: 99%